A Review Of Second Language Teaching And Learning Through Short Fiction And Communicative Approach - Dr. Tariq Khan (University of Chitral Journal of Linguistics and Literature, 2019)
This paper examines the potential role of literature and Communicative Approach in teaching second language (SL). This paper mainly focuses on digging out the prospective role of literature and Communicative Approach in teaching SL. Analysis of past studies indicate that teacher usually recourse to Grammar Translation Method for teaching of English language, for this method needs little endeavor and supplementary materials[1]. The reviewed literature has found that this method is ineffective and futile. To critically examine the potential role of literature in combination with Communicative Approach in teaching SL, this paper tries to unearth the current literature and investigates the relevant research works carried out on the importance of exploiting Literature and Communicative Approach for teaching of English language. The present paper found that using literature and communicative approach for teaching of SL is more effective and productive than GTM. In the light of findings of this study, it is recommended that teachers of L2 need to exploit literature and employ Communicative Approach for teaching of second language.